Elemental cloth - Cason, Cory Jo, author; Lundberg, Thomas R., advisor; Coronel, Patricia D., committee member; Voss, Gary Wayne, committee member; Clemons, Stephanie, committee member (Colorado State University. Libraries, 2007)
Cloth is elemental. In its most basic form, it is created by interlacing threads in an over-under construction. Individual threads are woven together to create a substantive piece of cloth, and the result can be uncomplicated and beautiful. Elemental or basic, uncompounded visual form has the potential to be beautiful in its simplicity. Using only components deemed essential, I endeavor to create a visual experience with elegant directness and a quiet presence that arises from this idea of unassuming simplicity. My weavings focus on the essential, the elemental, and the inherent beauty found in visual simplicity. I use cloth to inhabit, divide, and shape interior architectural space. Acting as architectural markers, the weavings delineate space and guide viewer movement. It is important for me to create an overall atmosphere, as well as to provide engaging visual details. It is my intent to create a space that is refined in its simplicity, where stillness and silence are tangible. Architecture, spatial organization, movement, and color are specifically related to the viewer's experience and also described within the microcosm of the constructed cloth. The influence of architecture is evident in my work. I am particularly interested in twentieth century modern architecture. Cleanness of line, exactness of expression and use of industrial materials are aligned with my central idea of simplicity and visual economy. These characteristics influence the overall organization of the complete space and the design of the individual weavings. The two-dimensional weavings work together to create a three dimensional space. They act as an architectural construction that creates a distinct space through which viewers can move. The influence of architecture is also seen in the strong verticality and large scale of the weavings. The use of concrete, a material known for its economy and basic building applications, is a suitable companion for the cloth; both are inherently elemental in their nature. The weavings are grounded by their placement over concrete bases, reminiscent of architectural bases with columns or pillars. The spatial organization of woven fabric panels guides viewers through the work. By moving through the space, viewers can change their perspectives on the complete space as well as their proximity to the individual weavings. The small spatial gaps that occur in the weave of the cloth allow light and air to become components of the piece. This transparency encourages the layers of cloth to optically overlap and increases spatial depth. Viewers can affect the space by their own movement. Encouraged by the warmth of the material and innate human connections to the cloth, viewers can move throughout the space to take a closer look. The weavings are light and airy, and the space is activated as cloth sways with movement of the viewer. Movement is also present in specific fabric details. I use the ikat-dyeing technique to accentuate the vertical movement of the warp threads, in contrast to the less active unmarked space in the cloth. Ikat also marks the movement of the horizontal weft across the fabric, where one might see staccato marks or more lingering dashes. This technique allows me to reinforce and highlight the elemental nature of the cloth construction. The reduced color palette of blues, grays, whites and blacks acts to provide cohesion for the piece and sets the emotive tone of the space. A serious and contemplative color, blue fills the space with a quiet calm and stillness. This color palette evokes a sense of an expansive outside space effecting an atmospheric quality, while complementing the color of concrete and emphasizing economy and simplicity. The color relationships within the cloth highlight visual transition and emphasize transparency and lightness. I am drawn to visual simplicity and the creative potential it holds. Cloth, which is inherently elemental, is the form I have chosen to explore this idea. My weavings focus on the essential and the elemental, and I endeavor to create work that speaks with a quiet presence and that is beautiful in its simplicity.
Keywords: Textile fabrics